Hydrogeochemical and isotopic evaluation of groundwater with elevated arsenic in alkaline aquifers in Eastern Punjab, Pakistan. (June 2018) - Mushtaq, Nisbah; Younas, Ayesha; Mashiatullah, Azhar; Javed, Tariq; Ahmad, Arslan; Farooqi, Abida
Abstract: Geochemical investigation was carried out for delineating factors responsible for the mobilization of arsenic (As) from aquifer material into the groundwater. Four sites along Ravi River, ( Samada, Sarai Chimba, Kot Maiga and Chah Fatehwala), were selected based on the blanket survey. Groundwater-rock interaction and evaporation were the key phenomena controlling groundwater chemistry, as shown by the hydrogeochemical data. Groundwater was predominantly Na-Cl type, with other principle facies being Na-HCO3, Na-Ca-HCO3 and Ca-Mg-Cl. The groundwater As concentration ranged between below detection level (2 μg/L) to 548 μg/L with 59% samples exceeding the World Health Organization (WHO) guidelines for As in drinking water (10 μg/L) and 31% having higher concentrations than the National Environmental Quality Standard (NEQS, 50 μg/L). Moderate to high concentrations of SO4 −2 averaged at 244 mg/L and moderate NO3 − concentrations averaged at 8 mg/L, together with alkaline pH (7.3–8.8) and high Eh values (113–402 mV) suggest partial oxidizing nature of the aquifers. The values for δ 18 O and δ 2 H in groundwater varied between −9.14 and −5.51‰, and −56.57 to −39.5‰ respectively, and suggests meteoric origin of the groundwater with some evaporative loss. This effect could be partly responsible for elevated levels of pH and salinity in groundwater. Based on geochemical and isotopic composition of groundwater, desorption of As from metal surfaces under alkaline environment might be the factor causing As enrichment in study area. Highlights: Elevated levels of Arsenic are detected under partial oxidizing conditions. 59% of groundwater samples exceeded the WHO permissible limit of 10 μg/L for As. Groundwater isotopic composition indicated meteoric origin of groundwater recharge. Evaporative controls in addition to competitive desorption reactions are mainly controlling high arsenic levels in groundwater.